The Effect of two types from foliar feeding on some growth character-istics for Prunus mrianna - عبد الرحمن, سيناء; احمد هاشم, هناء; مدحت حسين, مواهب (Journal of Kerbala for Agricultural Sciences, 2017)
Experiment carried out at the Technical Institute of AL-Musayaib during the grow season 2014 on the seedlings of prunus mrianna .When were sprayed two types of foliar feeding the first factor spray seedling foliar feeding Black sea concentnations (0,0.5,1) g /L1- .the second factor was the concentration of foliar feeding Elodia (0,50 ,100,150) m/L1- the experiment as a factor random complete design with three replications and by three seedlings of per treatment and the results showed the following :- -Excellence level 1g/L1- of compost Blaek sea outweigh moral to than treatments and in all of the traits which gave respectively 124.91 and 12.47 and 116.15 and 26.93 and 17.94 and 33.66 and 1.23 plant height and number of branches ,number of leaves and area and weight dry and the proportion of the chlorophyll and the percentage of nitrogen .- showed the level 150 ml/L1-of fertilizer Elodia significant superiority on all treatment which gave the 127.62 and 13.14 and 123.46 and 23.98 and 18.13and 35.25and 1.27for recipes studied and respectively plant height and number of branches ,number of leaves and leaf area and dry weight ratio chlorophyll and the percentage of nitrogen .pravaleaya moral synthesis between (Black sea ,Elodia ) to give the high average growth for all growth indicators which gave the 132.14 and 138.01and 14.31 and 26.04 and 19.29 and 39.15 and 73.10 and respectively .